Raman Spectroscopy for Noninvasive Monitoring of Umbilical Cord Mesenchymal Stem Cells Viability Transitions - P.Chen; F.Zhang; L.Lin; H.Bai; L.Zhang; G.Q.Tang; H.Fang; G.G.Mu; Gong, W.; Liu, Z. P.; Han, Z. B.; Zhao, H.; et al. (IntechOpen, 2011)
None